The spatial pattern and influence mechanism of urban vitality: A case study of Changsha, China - Xia, Xiaojiang; Zhang, Yang; Zhang, Yue; Rao, Tiechuan (Frontiers in Environmental Science, 2022)
In the new era, the vitality of urban space is an important engine of urban development, and the improvement of urban space vitality is the core component of urban spatial structure optimisation and space renewal. However, the availability of data is an important issue in the evaluation of urban space vitality, and continuous vitality monitoring of the entire city is difficult to achieve through traditional methods of field research and questionnaire interviews. This challenge makes the traditional vitality assessment methods have serious limitations in the analysis of vitality causes and the guidance of urban space development. Using mobile phone signalling data, this study takes Changsha City as an example to measure the urban spatial vitality and uses the SEM model to analyse how market intervention, traffic accessibility and spatial characteristics affect the density and stability of urban spatial populations. Results show that the overall urban space vitality density and vitality stability demonstrates an obvious ‘centre-periphery’ pattern, and the vitality of the urban centre area is in a ‘high density–low stability’ state. The overall urban vitality density on rest days is slightly lower than that on weekday, and the stability of vitality on rest days is significantly higher than that on weekday. Market intervention and transportation accessibility support vitality density, but not vitality stability, and spatial characteristics are the opposite. The findings can provide insights relevant to urban spatial planning and design.